Digital transition and the clean renewable energy adoption in rural family: evidence from Broadband China - Yan, Jinchen; Li, Jing; Li, Xia; Liu, Yifang (Frontiers in Ecology and Evolution, 2023)
The ongoing digital transition and the pressing need for sustainable energy solutions have prompted increased interest in examining the impact of digital technologies on clean renewable energy adoption. However, a dearth of research focuses on energy consumption in rural households, particularly in developing countries like China. This study leverages the quasinatural experiment of the Broadband China Project (BCP) and utilizes data from the China Labor-force Dynamics Survey (CLDS) from 2012 to 2016 to investigate the effect of digital transition on clean renewable energy adoption in rural families. We employ staggered Differencein-Differences (DID) and Doubly Robust Staggered DID estimators to assess this impact and explore heterogeneity across regions. The findings demonstrate that the BCP significantly affects clean renewable energy adoption, but this effect varies across regions. In the middle region, implementing the BCP leads to a noteworthy 5.8% increase in clean renewable energy adoption compared to non-pilot cities. However, in the east and west regions, the BCP is associated with a decrease of 12.6% and 13.5%, respectively, in clean renewable energy adoption. Dynamic effect analysis reveals that the east region had already witnessed high clean renewable energy adoption before the BCP's implementation, whereas the BCP positively influences clean renewable energy intentions in the west region. Our analysis identifies three key channels through which the BCP impacts clean renewable energy adoption: population size, economic size, and income level. Larger populations and greater economic size enhance the BCP's impact on clean renewable energy adoption. These findings offer empirical evidence for developing countries seeking to harness digital development for technological progress, industrial upgrading, and carbon emission reduction. Policymakers can utilize these insights to design targeted interventions and policies that promote clean renewable energy adoption, foster sustainable energy practices, and enhance the well-being of rural residents.